Calling the shots on vaccination: when is the state justified in overturning a refusal to vaccinate? - Blignaut, Jessica (Department of Private Law, 2023)
Public perceptions of vaccination have changed greatly since George Bernard Shaw unleashed his diatribe against the practice. Today it is recognised that, far from spreading disease, vaccination is one of the cheapest and most effective public health interventions. Immunization against infectious diseases has drastically reduced mortality and morbidity, particularly among children, and has diminished the disease burden caused by poliomyelitis, rubella, measles, tetanus, diphtheria, and whooping cough, amongst others. By one estimation, paediatric immunization worldwide prevents approximately 3 million child deaths each year, and saves 750 000 more from disability.